2005
DOI: 10.1177/021849230501300406
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Pericardial Valved Conduit for the Ross Operation

Abstract: The feasibility and function of autologous pericardial valved conduit for right ventricular outflow tract reconstruction in the Ross operation were assessed. Between June 1997 and April 2002, 31 patients underwent this procedure at our institution; one was lost to follow-up. The other 26 males and 4 females were aged 17 to 60 years (mean, 36.6 years). Causes of aortic valve disease were infective endocarditis in 26 and rheumatic valve disease in 4. Mean follow-up was 16.7 months (range, 1-58 months). Preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The durability of these valves in the long term remains questionable however [8]. Several attempts have been made to construct a hand-fashioned autologous pericardial valved conduit intraoperatively [9][10][11][12][13][14]. All of them used some variation in suturing of the pericardial tissue to create a competent valve and conduit with limited long term success.…”
Section: Discussionmentioning
confidence: 99%
“…The durability of these valves in the long term remains questionable however [8]. Several attempts have been made to construct a hand-fashioned autologous pericardial valved conduit intraoperatively [9][10][11][12][13][14]. All of them used some variation in suturing of the pericardial tissue to create a competent valve and conduit with limited long term success.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts were made to construct a hand-fashioned autologous pericardial valved conduit intraoperatively [2,12,10,[22][23][24][25]. The methods were time-consuming and not always reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, Chotivatanapong et al reported a technique using autologous pericardium to create a pulmonary valved conduit for the Ross operation. 9 Their technique involves a rather complicated and time-consuming process.…”
Section: Commentmentioning
confidence: 99%